Exploring labour and birth experience and relationships with maternal sleep and symptoms of postnatal mental distress in Aotearoa/New Zealand : a mixed methods study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Auckland, New Zealand - Job, Kirsty Annetta (Massey University, 2022)
Labour and birth experience (birth experience) can significantly affect a woman's wellbeing; however, there is a dearth of research on the prevalence and implications of a positive or negative experience in Aotearoa/New Zealand. Good sleep health is vital for mental health; however, whether sleep is a pathway linking labour and birth experience and postnatal mental distress is unclear. This mixed methods study was guided by a social determinants of mental health theoretical lens. It investigated Māori and non-Māori women’s birth experiences and relationships between birth experience, maternal sleep, and postnatal mental distress, using data from the Moe Kura study, which is informed by Kaupapa Māori epidemiological principles. Quantitative data (Māori: n = 383, non-Māori: n = 702) were analysed using descriptive statistics and hierarchical logistic regression. Approximately one-third of women reported a negative birth experience, which was associated with anxiety symptoms at 4-6 weeks postpartum and more severe mental distress symptoms at 11-13 weeks postpartum. Māori women were over-represented in more socioeconomically deprived areas and were more likely to experience stressful life events and birth in a place different to planned. Antenatal mental distress was consistently associated with postnatal mental distress. Sleep was independently associated with postnatal mental distress at 11-13 weeks postpartum but did not attenuate associations between birth experience and postnatal mental distress. A sub-sample of 13 Māori and 87 non-Māori women commented on their birth experience. Qualitative content analysis identified four themes: reactions 'expressing myself’, appraisals ‘into the unknown’, aspects 'reality of experience’, and impact on future labour and birth decisions and experiences 'looking ahead.’ Differences in experiential patterns included negative experiences around communication and obstetric interventions described by Māori women and contrasting expectations versus reality of birth experience described by non-Māori women. Mixed methods findings indicated that although many women report a positive birth experience, a considerable proportion have a negative experience which may increase risk of postnatal mental distress. Good sleep health is important for postnatal mental health but may not be the primary pathway linking birth experience to mental distress. Structural drivers of social and maternity service inequities must be addressed to achieve equitable maternal mental health.
Keywords: 520304 Health psychology